State-of-the-art in terahertz sensing for food and water security – A comprehensive review. (March 2019) - Ren, Aifeng; Zahid, Adnan; Fan, Dou; Yang, Xiaodong; Imran, Muhammad Ali; Alomainy, Akram; Abbasi, Qammer H.
Abstract: Background: Recently, there has been a dramatic change in the field of terahertz (THz) technology. The recent advancements in the THz radiation sector considering generation, manipulation and detection have brought revolution in this field, which enable the integration of THz sensing systems into real-world. The THz technology presents detection techniques and various issues, while providing significant opportunities for sensing food and water contamination detection. Scope and approach: Many researchers around the world have exploited the potential of invaluable new applications of THz sensing ranging from surveillance, healthcare and recently for food and water contamination detection. The microbial pollution in water and food is one the crucial issues with regard to the sanitary state for drinking water and daily consumption of food. To address this risk, the detection of microbial contamination is of utmost importance, since the consumption of insanitary or unhygienic food can lead to catastrophic illness. Key findings and conclusions: This paper presents a first-time review of the open literature covering the advances in the THz sensing for microbiological contamination of food and water, in addition to state-of-the-art in network architectures, applications and recent industrial developments. With unique superiority, the THz non-destructive detection technology in food inspection and water contamination detection is emerging as a new area of study. With the great progress, some important challenges and future research directions are presented within the field. Highlights: Microbial pollution is one crucial issues on sanitary state of water and food. THz detection technologies are potential for being addressed to identify contaminants. Review of open literature covering THz research sensing for contamination detection. Open challenges and research directions within this area are proposed.